Evaluation of an fMRI USPIO‐based assay in healthy human volunteers. Issue 1 (24th October 2016) - Baumgartner, Richard; Cho, William; Coimbra, Alexandre; Chen, Christopher; Wang, Zaiqi; Struyk, Arie; Venketasubramanian, Narayanaswamy; Low, May; Gargano, Cindy; Zhao, Fuqiang; Williams, Donald; Reese, Torsten; et al.
Abstract : Purpose: To present the testretest and contrast dose effect results of cerebral blood volume (CBV) functional MRI (fMRI) in healthy human volunteers using ferumoxytol (Feraheme), an ultrasmall‐superparamagnetic iron oxide (USPIO) nanoparticle. Materials and Methods: This was an open‐label, two‐period, fixed‐sequence study in healthy young volunteers. In eight subjects, using a 3 Tesla field strength system, blood oxygen level dependent (BOLD) and CBV fMRI were acquired in response to a visual black‐and‐white checkboard stimulation paradigm using an escalating ferumoxytol dose design (250, 350, and 510 mg iron). Multiple outcome measures were analyzed including absolute percent signal change (|PSC|, primary endpoint), its contrast‐to‐noise ratio (CNR) and corresponding z‐score, percent CBV change (ΔCBV) and respective CNR, concentration of Fe, and baseline CBV. Results: The |PSC| in the visual cortex increased with ferumoxytol dose and was up to 3 × higher than BOLD fMRI. Test–retest reliability was comparable for BOLD and CBV fMRI. Intraclass correlation coefficients (ICCs) for |PSC| were 0.3 (one‐sided 95% lower confidence limit = 0.00), 0.81 (0.47), 0.48 (0.00), and 0.3 (0.00) for BOLD and the 250‐, 350‐, and 510‐mg doses of ferumoxytol, respectively. For ΔCBV, ICCs were 0.77 (0.37), 0.48 (0.00), and 0.49 (0.00) for 250 mg, 350 mg, and 510 mg, respectively. Conclusion: This work demonstrates that CBV fMRI techniques and endpoints are dose dependent, robust and have good test–retest repeatability. It also confirms previous findings that USPIO enhances sensitivity of fMRI stimulus‐response endpoints. Level of Evidence: 1 J. MAGN. RESON. IMAGING 2017;46:124–133